CONSTITUTIONAL FOUNDATIONS OF MODERN STATE IN THE REGIONAL PRIVILEGES OF THE GRAND DUTCHY OF LITHUANIA - Machovenko, Jevgenij (Teisė, 2015)
The results of the analysis of the regional privileges of the Grand Dutchy of Lithuania (hereinafter referred to as GDL), carried out within the scope the research on the history of Lithuanian constitutionality, are presented in the article. Provisions, which are the basis of construction and functioning of the modern state power – the nation‘s sovereignty, separation of powers, rule of law, parliamentarianism, etc., are identified in the regional privileges of GDL. It is inferred, that from the legal point of view all the regional privileges in GDL issued in 1387–1568 were the sources of constitutional law (constitutional legal acts) in the modern sense of the term. The legal connection between the regional privileges and actual Constitution of the Republic of Lithuania is revealed.